PELATIHAN PEMBUATAN BUKU DIGITAL BERBANTUAN FLIPBOOK MAKER SEBAGAI BAHAN AJAR INOVATIF BAGI GURU DI SMP NEGERI BUTI - Irmawaty Natsir; Abdul Rachman Taufik; Maria Fransina V. Ruslau (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Digital books are a collection of texts that utilize technology to convey information in a shorter and non-static form where digital books are able to combine sound, graphics, images, animation, and video so that the information presented is more diverse. One application that can be used in making digital books is Flipbook. Flipbook is an application for creating digital books that not only contain text but can be inserted with pictures, graphics, sound, links, and videos so that the appearance of the book becomes more attractive. This activity aims to train teachers' abilities and skills in making digital books that are designed by themselves using applications/software. Training on making digital books will be held at SMP Negeri Buti. The training activity will begin with an explanation of digital books and applications/software that can be used in making digital books, demonstrations by presenters of the stages in designing digital books, followed by the practice of making digital books using Flipbooks. The results of the training activities received a positive response from the training participants